Cultural Consumption as a means for International Tourist development. An analysis applied to Villavicencio – Colombia (Encuentros, 2017)
This article analyses the international touristic flows and their relation with cultural consumption by keeping into account the qualification given by consumers to Villavicencio - Colombia as a tourist destination. Three dimensions were taken into account: 1) image perception of the cultural destination, 2) perceived quality of the destination, and 3) satisfaction levels based on cultural consumption. This is a quantitative work based on the correlational analysis of variables, taking 121 international tourists as sample size. It outlines the fact that the consumer significantly values traditional food and traditional dance, but the same doesn’t happen with autochthonous sports. The possibilities of recommending the destination to promote cultural consumption are high.